Teori Belajar Humanistik dan Implikasinya Dalam Pembelajaran - Rahman, Aulia; Hayati, Mufidah; Rusmani, Muhammad Afdhal; Ilmi, Darul (ANTHOR: Education and Learning Journal, 2023)
Lack of understanding of the purpose of the learning process, in the end, students only compete for the best grades regardless of how it is applied. Humanistic learning theory is a learning model that emphasizes humanizing students, taking into account meeting the needs of students in learning. Humanistic theory is a learning concept that explains how to humanize students and actualize all potential abilities of each learner to deal with changes in the surrounding environment. This theory assumesthat learning will not be meaningful if there is coercion in it. This paper attempts to examine humanistic learning theory and its implications for learning. The application of humanistic learning theory and its implications for learning can bedone by providing evidence of Islamic teachings, humanistic theory can be done with creative, active, fun, contextual, and cooperative learning strategies. The concept of humanistic learning theory is a learning process aimed at humanizing humans, learning success is marked when students recognize themselves and their environment well.